THE MARK OF ATHENA - Riordan, Rick, 1964-, author 407413 (New York, NY : Scholastic Inc., 2014)
The Greek and Roman demigods will have to cooperate in order to defeat the giants released by the Earth Mother, Gaea. Then they will have to sail together to the ancient land, Greece itself to find the Doors of Death.